Surface from Under the Microscope: The Henrietta Lacks Series (The National Academies Press, 2020)

Sagehen: A Sierra Proving Ground (The National Academies Press, 2022)

Arctic Ice: A Visual Archive: A unique collaboration among Cy Keener, Justine Holzman, Ignatius Rigor, and John Woods (The National Academies Press, 2023)
From September 15, 2022, through February 15, 2023, Cultural Programs of the National Academy of Sciences presented the exhibition Arctic Ice: A Visual Archive. It featured two new bodies of work - Iceberg Portraiture and Sea Ice Daily Drawings - integrating field data, remote satellite imagery, scientific analysis, and multimedia visual representation to document Arctic ice that is disappearing due to climate change. The work was the outcome of a four-year collaboration spanning art, design, and polar science between artist Cy Keener, landscape researcher Justine Holzman, climatologist Ignatius Rigor, and scientist John Woods. With this work, the collaborators goal is to make scientific data tangible, visceral, and experiential. Much of what researchers know about the oceans and about sea ice has been gained through environmental modeling devices, deployed at different times in different locations. When combined, this data becomes the substance of complex and ever-evolving scientific research. This exhibition provides a small window into the datasets that compose climate science. This publication is a documentation of the exhibition and features an essay by Ignatius Rigor and an interview with Cy Keener and Justine Holzman.

Chaosmosis: Assigning Rhythm to the Turbulent (The National Academies Press, 2023)
This catalog documents Chaosmosis: Assigning Rhythm to the Turbulent, an art exhibition inspired by fluid dynamics, a discipline that describes the flow of liquids and gases. The exhibition draws from past submissions to the American Physical Society’s Gallery of Fluid Motion, an annual program that serves as a visual record of the aesthetic and science of contemporary fluid dynamics. The submissions were curated into an educational art exhibition to engage viewers’ senses. The exhibition was on view at the National Academy of Sciences from October 2, 2023, through February 23, 2024. The catalog features an essay by Azar Panah, an Associate Professor in Mechanical Engineering at Penn State University at Berks and Coordinator of the Gallery of Fluid Motion at the American Physical Society’s Division of Fluid Dynamics; and an essay by the exhibition’s curators, Natalia Almonte and Nicole Economides.